The tarsal tunnel syndrome in hypothyroidism. - Schwartz, M S (1983)
Nine patients with myxoedema and carpal tunnel syndrome have been studied clinically and electrophysiologically to determine the presence or absence of the tarsal tunnel syndrome. Four patients had electrophysiological evidence of the tarsal tunnel syndrome, three of whom were mildly symptomatic. This would suggest that the tarsal tunnel syndrome is frequently encountered in myxoedema in association with the carpal tunnel syndrome.